2013
DOI: 10.1177/0146167213479612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Implementation Intentions on Anxiety, Perceived Proximity, and Motor Performance

Abstract: Anxiety leads to exaggerated perceptions of distance, which may impair performance on a physical task. In two studies, we tested one strategy to reduce anxiety and induce perceived proximity to increase performance. We predicted implementation intentions that reduce anxiety would increase perceived visual proximity to goal-relevant targets, which would indirectly improve performance. In two studies, we induced performance anxiety on a physical task. Participants who formed implementation intentions to reduce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
(87 reference statements)
2
22
0
1
Order By: Relevance
“…Second, we use counterintuitive behavioral responses as dependent measures, such that even if participants guessed the purpose of the study, they would not know how to respond to support the hypotheses (e.g., Balcetis & Dunning 2010;Stern et al 2013). For example, participants estimated the distance to a desirable (chocolates) or undesirable object (dog feces) by moving themselves to stand a set, referent distance away from it (Balcetis & Dunning 2010, Study 3b).…”
Section: Open Peer Commentarymentioning
confidence: 99%
“…Second, we use counterintuitive behavioral responses as dependent measures, such that even if participants guessed the purpose of the study, they would not know how to respond to support the hypotheses (e.g., Balcetis & Dunning 2010;Stern et al 2013). For example, participants estimated the distance to a desirable (chocolates) or undesirable object (dog feces) by moving themselves to stand a set, referent distance away from it (Balcetis & Dunning 2010, Study 3b).…”
Section: Open Peer Commentarymentioning
confidence: 99%
“…Moreover, detailed studies on the effects of perceptual biases on motor behavior that include kinematics and performance outcomes would be useful. Stern et al [22] indicated that reducing anxiety under pressure by using an implementation intention strategy led to performance improvements along with compensation for the distance perception bias in golf-putting and dart-throwing tasks. This suggests that psychological skills for reducing state anxiety might play a key role in developing optimal perception and action under high pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Bieleke et al (2020) argue that the effectiveness of if-then plans might be enhanced by tailoring if-then plans to athletesthat is, instructing exercisers to generate their own plan contents geared towards their personal obstacles and strategies to deal with them. For example, studies using if-then plans with no particular obstacle in non-endurance domains (e.g., Tennis; Achtziger et al, 2008;or Golf and Darts;Stern et al, 2013) observed rather consistent positive effects on performance. In the present study, we therefore utilized the information on obstacles and strategies that we elicited from participants to help exercisers generate individually tailored if-then plans.…”
Section: Optimizing Performance With Tailored Self-regulatory Intervementioning
confidence: 99%
“…Based on the previously observed biennial effects of self-generated if-then planning on performance (Achtziger et al, 2008;Stern et al, 2013), we expected that this approach leads to improved performance in the if-then plan condition compared to the goal intention condition in the second session.…”
Section: The Present Studymentioning
confidence: 99%